A Longitudinal Academic Career Skills Elective Experience - Christopher Weaver; Carey Chisholm; Kevin Rodgers (Association of American Medical Colleges, 2009)
Abstract Introduction Residency programs have the potential to cultivate increased enthusiasm for academics and to improve the preparedness of graduates to succeed in such a career. Indiana University School of Medicine Department of Emergency Medicine employs a 1-year longitudinal elective designed to provide interested residents with the opportunity to learn about important skills needed for success in academics. Methods This publication outlines the timeline of the curriculum and the list of topics discussed. Each topic has a list of goals and objectives, and a suggested reading list. The curriculum includes a variety of learning venues including 10 preceptor teaching shifts in the emergency department, small-group discussion sessions to discuss teaching dilemmas, programmed readings, and focused workshops. After each preceptor shift, selected faculty provide feedback about content and quality of clinical teaching and assessment/grading of the learners. Results This elective has been offered to senior residents in our 3-year emergency medicine and emergency medicine/pediatrics residency programs. The elective is completed by a varying number of residents (range 4-8), fellows (range 2-3), and junior faculty (range 2-5) each year. Between 2000 and 2005, the 21 residents who completed the elective rated the overall experience as a 9.1 on average (10-point scale). Each participant who has completed the elective has rated it to have contributed significantly to their preparedness for a career in academic medicine. Of those who completed the elective, 67% (14/21) entered an academic career path as compared to 8% (5/65) of those residents who graduated from the residency during the same time period but did not choose this as an elective experience. Discussion Lectures and readings offer knowledge of teaching, research, and presentation methodology but participants value the hands on experience and interactive discussions to draw from the experience of the group and test what they have learned with their own teaching experiences. The implementation of such a program may increase the enthusiasm for academics and will aid to build the skill set necessary for success.